Patterns of Antihypertensive Medication Utilization Among Hypertensive Patients: A Review of Single-Therapy Practices in Outpatient Primary Healthcare Centers - Fendy Prasetyawan; Yuneka Saristiana; Faisal Akhmal Muslikh; Chandra Arifin; Abd Rofiq; Elsa Mahardika Putri; Anis Akhwan Dhafin (Journal Health of Indonesian, 2024)
Hypertension, often referred to as "The Silent Disease," presents a significant global health challenge due to its asymptomatic nature and association with severe cardiovascular complications. Effective management of hypertension primarily relies on the administration of antihypertensive drugs, either as monotherapy or combination therapy. This study investigates the utilization patterns of single antihypertensive drugs among hypertensive patients in the outpatient setting of Puskesmas "X" in Solo City. Utilizing a retrospective approach, data from patient medical records were analyzed to examine drug usage patterns and patient responses to therapy. Results revealed a noteworthy preference for combination therapy, with approximately 64.18% of patients opting for this approach. Combination therapy strategies were favored due to their additive and synergistic effects, potential for reducing side effects, and enhanced blood pressure control. Specifically, amlodipine from the calcium channel blocker (CCB) group emerged as the most commonly prescribed single antihypertensive drug, while the combination of amlodipine with candesartan from the angiotensin receptor blocker (ARB) group was the predominant combination therapy. These findings align with previous research, emphasizing the significance of combination therapies in hypertension management..